Biofilms, mobile genetic elements and the persistence of pathogens on environmental surfaces in healthcare and food processing environments - Nkemngong, Carine; Teska, Peter (Frontiers in Microbiology, 2024)
Biofilms are the natural state for bacterial and fungal species. To achieve surface hygiene in commercial facilities, the presence of biofilms must be adequately considered. However, standard disinfectant and sanitizer efficacy tests required by the US-EPA and the European Committee for Standardization (CEN) do not currently consider the role of environmental biofilms. This selective review will discuss what biofilms are and why they are important. We will also cover where they are commonly found in healthcare and food processing facilities and explore how current antimicrobial test methods required for product registration do not test for the presence of biofilms.Additionally, we will explore how a lack of efficacy against biofilms may play a role in the development of antibiotic resistance in healthcare facilities due to the exchange of mobile genetic elements that occur readily in a biofilm matrix.